Path analysis of adolescents’ reproductive health education on college students’ sexual behavior - Arifah, Izzatul; Werdani, Kusuma Estu (Intelektual Pustaka Media Utama, 2023)
Young people are vulnerable to reproductive health (RH) problems due to their engagement in risky sexual behavior. Study of adolescents’ RH education effects on the behavior of the young will add evidence about aspects that directly/indirectly affect the behavior. This study intended to explore the influence of adolescents’ RH education and other associated factors on college students’ sexual behavior using path analysis. A cross-sectional study was conducted from March to Mei 2021 in Solo Raya Residency, Central Java, Indonesia. A sample of 20-24 years old college students from public dan two private universities (n=375) participated. An online questionnaire was used to collect the data. Path analysis was conducted to identify relationships between variables. Path analysis demonstrated that sexual behavior was directly affected by age and pornography access, regardless the gender. Even though factors that influenced sexual behavior differed among female and male students, RH education was proved to indirectly influence sexual behavior irrespective the gender. Overall, sexual behavior was influenced by RH education in the complex mechanism. Improving the information delivery of RH education is needed to ensure all youth, irrespective of gender, benefit from this program. Further study in a more significant setting in Indonesia is required.